Intensive Care and Treatment of Severe Guillain–Barré Syndrome - Shang, Pei; Feng, Jiachun; Wu, Wei; Zhang, Hong-Liang (Frontiers in Pharmacology, 2021)
Guillain–Barré syndrome (GBS) is an acute polyneuropathy mostly characterized by acute flaccid paralysis with or without sensory/autonomous nerve dysfunction. Up to 30% of patients develop respiratory failure during hospitalization requiring mechanical ventilation and intensive care. In contrast with immunotherapies, tracheostomy and supportive care are largely empirical for severe GBS cases. Current therapies including intravenous immunoglobulin (IVIg), plasma exchange (PE), and newly-developed biological drugs benefit patients by alleviating hyperreactive immune responses. Immunotherapies, mechanical ventilation, supportive care, and complication management during intensive care unit (ICU) stay are equally emphasized in severe GBS cases. In this narrative review, we summarize up-to-date knowledge of pharmacological therapies and ICU management of patients with severe GBS. We aim to answer some key clinical questions related to the management of severe GBS patients including but not limited to: IVIg better than PE or vice versa? Whether combinations of immune therapies benefit more? What are the emerging therapies promising for GBS? When to perform tracheal intubation or tracheostomy? How to provide multidisciplinary supportive care for severe cases? How to avert life-threatening complications in severe cases?